Comparison of Male Reproductive Performance with Naturally Mated and Superovulated Female Mice - Cheng Yeow Koon (2018)
Superovulation is integrated in Assisted Reproductive Technology prior cryopreservation. It is a procedure that exogenous gonadotrophins such as pregnant mares’ serum gonadotrophin or follicle stimulating hormone followed by human chorionic gonadotrophin administrated to the female mice for producing large numbers of embryos. Superovulation reduces the number of animal used while increase the number of oocyte or embryo production. In this study, the reproductive performance of male mice was conducted using superovulated (SO) mice and naturally mated (NM) mice, also the optimal male semen condition was determined by observing the number of sample presented. The study investigated the factor that affecting the mice performance. Furthermore, the vaginal copulatory plug was an important element for a successful mating. Limitation of the study was investigating on ICR breed mice and limited time for mating 20 female mice in 2 weeks. As result, the SO mice successful to produce more sample (n=106) comparing NM mice (n=75) in number. The semen condition which dilute produce only oocyte (0% embryo produced) while high amount of embryo was discovered in the hard solid condition for SO mice (73% embryo produced) and NM mice (100% embryo produced).